2019
DOI: 10.4236/jbm.2019.74003
|View full text |Cite
|
Sign up to set email alerts
|

Self Ear Cleaning: Prevalence and Profile among School Children in Ekiti, Nigeria

Abstract: Background: Self-cleaning of ears with different objects is a common practice among school children with scanty report in literature. Aim: The aim of this study was to determine the prevalence and profile of self-ear cleaning among school children. Methods: It was a cross-sectional institutional-based study which was carried out among school children in Ekiti, south western Nigeria from January 2017, to March 2017. Results: A total of 174 students participated in this study. Their age ranged between 13 and 17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
2
0
3
Order By: Relevance
“…In another South African study conducted in one of the local universities, Khan, Thaver and Govender (2017) found that almost every student interviewed was engaging in self-ear cleaning, with a majority of them (79.6%) using cotton buds. These ear care practices have been shown to cause ear-related injuries (Olajide et al 2019), which may include tympanic membrane perforations (Khan et al 2017).…”
Section: Chaptermentioning
confidence: 99%
“…In another South African study conducted in one of the local universities, Khan, Thaver and Govender (2017) found that almost every student interviewed was engaging in self-ear cleaning, with a majority of them (79.6%) using cotton buds. These ear care practices have been shown to cause ear-related injuries (Olajide et al 2019), which may include tympanic membrane perforations (Khan et al 2017).…”
Section: Chaptermentioning
confidence: 99%
“…Trauma pada epitel dapat memicu terjadinya infeksi dengan mudah, terutama apabila benda yang dimasukkan mengandung elemen bakteri dan fungi. [5][6][7][8][9] Menurut teori oleh Green dkk., perilaku masyarakat dipengaruhi oleh faktor predisposisi (predisposing factor), salah satunya adalah pengetahuan. 10 Pengetahuan yang kurang mengenai pentingnya serumen dapat menimbulkan praktik membersihkan telinga yang salah.…”
Section: Pendahuluanunclassified
“…Kuesioner ini diadaptasi dari studi terdahulu. 6,7 Penelitian ini berlangsung dari bulan Februari hingga Agustus 2021.…”
Section: Penelitian Ini Merupakan Studi Potong Lintang (Crosssectional)unclassified
See 1 more Smart Citation
“…The attitude, awareness and knowledge of the public regarding health hazards and complications of self-ear cleaning are very poor, as there is a common belief that it is beneficial (Afolabi et al, 2009). Many studies have reported poor knowledge regarding self-ear cleaning worldwide (Alateeq et al, 2018;Ghauth et al, 2018;Lukolo et al, 2021;Olajide et al, 2019;Tobih et al, 2021). A study conducted in the Makkah region on a young population demonstrated that 80% of participants had poor knowledge and 60% of them would not consult a doctor if they experienced hearing difficulties (Haji et al, 2021).…”
Section: Introductionmentioning
confidence: 99%